Assembly and Analysis of Differential Transcriptome Responses of Hevea brasiliensis on Interaction with Microcyclus ulei. - Uriel Alonso Hurtado Páez; Ibonne Aydee García Romero; Silvia Restrepo Restrepo; Fabio Ancizar Aristizábal Gutiérrez; Dolly Montoya Castaño (PLoS ONE, 2015)
Natural rubber (Hevea brasiliensis) is a tropical tree used commercially for the production of latex, from which 40,000 products are generated. The fungus Microcyclus ulei infects this tree, causing South American leaf blight (SALB) disease. This disease causes developmental delays and significant crop losses, thereby decreasing the production of latex. Currently several groups are working on obtaining clones of rubber tree with durable resistance to SALB through the use of extensive molecular biology techniques. In this study, we used a secondary clone that was resistant to M. ulei isolate GCL012. This clone, FX 3864 was obtained by crossing between clones PB 86 and B 38 (H. brasiliensis x H. brasiliensis). RNA-Seq high-throughput sequencing technology was used to analyze the differential expression of the FX 3864 clone transcriptome at 0 and 48 h post infection (hpi) with the M. ulei isolate GCL012. A total of 158,134,220 reads were assembled using the de novo assembly strategy to generate 90,775 contigs with an N50 of 1672. Using a reference-based assembly, 76,278 contigs were generated with an N50 of 1324. We identified 86 differentially expressed genes associated with the defense response of FX 3864 to GCL012. Seven putative genes members of the AP2/ERF ethylene (ET)-dependent superfamily were found to be down-regulated. An increase in salicylic acid (SA) was associated with the up-regulation of three genes involved in cell wall synthesis and remodeling, as well as in the down-regulation of the putative gene CPR5. The defense response of FX 3864 against the GCL012 isolate was associated with the antagonistic SA, ET and jasmonic acid (JA) pathways. These responses are characteristic of plant resistance to biotrophic pathogens.